What is climate-smart agriculture? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
A short video about climate-smart agriculture (CSA) and how can it alleviate the effects of climate change in our world. Climate-smart agriculture is a way of attaining sustainable agricultural development amid climate change that aims to ensure food security through improved and sustainable agricultural productivity, build capacity towards climate resiliency and adaptation, and mitigate emissions of greenhouse gases.